Engineering study on harnessing energy using micro hydropower from untapped urban infrastructures - Lim, Bao Jie (Nanyang Technological University, 2023)
In Singapore, the use of hydropower technology is not feasible due to the lack of fast flowing water. However, this project will explore the feasibility of installing pico-hydropower system and harnessing the flow of water from the inlet of water storage tank located in HDB rooftop. The power harnessed could be used for providing electricity in common areas such as the ceiling LED lightings that are low consumption in electricity. This alternative source of energy could be an add-on to the alternative source of energy for the country.